First report of the Asian tapeworm Schyzocotyle acheilognathi in the Colombian freshwater fish Parodon magdalenensis - Rave, Astrid; López-Osorio, Sara; Uribe, Manuel; Hermosilla, Carlos; Chaparro-Gutiérrez, Jenny J. (Frontiers in Veterinary Science, 2025)
The Asian fish tapeworm (AFT), scientifically known as Schyzocotyle acheilognathi, is a commonly encountered invasive parasite that has great relevance in freshwater ecosystems. This euryxenous cestode has a complex life cycle and includes a wide range of definitive hosts. It has also been reported in more than 300 species of free-living and farmed fish, amphibians, reptiles, and birds. Its remarkable pathogenicity leads to high mortality rates in infected fish, particularly among cyprinids. The environmental adaptability of S. acheilognathi has contributed to its global spread across continents, excluding Antarctica. In South America, S. acheilognathi has been reported in Brazil and Argentina. In this study, we examined 103 specimens of Parodon magdalenensis, a hyperendemic characiform fish species native to the Magdalena River basin in Colombia, and found a parasite prevalence in 32 of 103 specimens (31.07%). This study presents the first morphological and molecular characterization of the AFT in Colombia and its identification in a new host species (P. magdalenensis), supported by rDNA sequences from the 28S, 18S, and 16S regions.